2015
DOI: 10.1007/s11999-014-3947-5
|View full text |Cite
|
Sign up to set email alerts
|

Do Laterally Wedged Insoles or Valgus Braces Unload the Medial Compartment of the Knee in Patients With Osteoarthritis?

Abstract: Background The results of conservative treatment of knee osteoarthritis (OA) are generally evaluated in epidemiological studies with clinical outcome measures as primary outcomes. Biomechanical evaluation of orthoses shows that there are potentially beneficial biomechanical changes to joint loading; however, evaluation in relation to clinical outcome measures in longitudinal studies is needed. Questions/purposes We asked (1) is there an immediate effect on gait in patients using a laterally wedged insole or va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 27 publications
1
41
0
3
Order By: Relevance
“…Biomechanical variables that were reported in more than 10 studies included the KAM (26/27 studies), gait speed (17/27 studies) and the frontal plane ankle moment (11/27 studies), while 21 different variables appeared in only one study. The number of different variables from a given study ranged from 114 to 30 15. Data are summarised in table 2 and Appendix 1, and summaries by intervention are listed below.…”
Section: Resultsmentioning
confidence: 99%
“…Biomechanical variables that were reported in more than 10 studies included the KAM (26/27 studies), gait speed (17/27 studies) and the frontal plane ankle moment (11/27 studies), while 21 different variables appeared in only one study. The number of different variables from a given study ranged from 114 to 30 15. Data are summarised in table 2 and Appendix 1, and summaries by intervention are listed below.…”
Section: Resultsmentioning
confidence: 99%
“…The 18 eligible studies included a total of 534 participants. All but 4 studies were withinsubjects repeated-measures designs, with the remaining being randomized trials (30)(31)(32)(33). Four studies reported the use of the ACR criteria (31,(34)(35)(36), with 10 stating cutoffs regarding the severity of knee pain (13,14,21,31,32,34,(36)(37)(38)(39), most commonly .3 of 10 on a visual analog scale (13,14,21,31,32,34,37).…”
mentioning
confidence: 99%
“…Fourteen studies prescribed the same insole to all participants, with the remaining 4 using a customized amount based on comfort and/or pain level (14,31,35,37). A flat insole was the comparison condition in 4 studies (14,31,34,37), 7 studies used participants' own footwear (13,21,30,32,36,40,43), 5 studies used standardized footwear (29,33,35,39,42), 1 study used both a flat insole and participants' own footwear (39), and 1 study did not report the type of footwear (41). Walking speed was either controlled across conditions within a threshold of each participants' preferred speed (13,14,21,31,32,37), (43).…”
mentioning
confidence: 99%
“…Было также выдвинуто предположение, что снижение аддукционного момента может быть достигнуто за счет физической реабилитации и тренировки мышц, однако анализ проведенных исследований с участием 233 пациентов не нашел подтвержде-ния данной гипотезы [15]. Но значительные из-менения величины медиального момента были достигнуты за счет использования различных ор-топедических изделий [14,[16][17][18].…”
Section: Introductionunclassified
“…Например, ортопеды для исправления начального вальгусного искрив-ления голеностопного сустава используют кор-ректирующие стельки, благодаря которым может быть уменьшен аддукционный момент коленного сустава за счет коррекции переката центра масс стопы (рис. 1) [16,17].…”
Section: Introductionunclassified